Polyethyleneimine methylenecarboxylate: a macromolecular DTPA analogue to chelate plutonium(iv). Issue 83 (2nd October 2018) - Lahrouch, Florian; Siberchicot, Bruno; Leost, Laurane; Aupiais, Jean; Rossberg, André; Hennig, Christoph; Den Auwer, Christophe; Di Giorgio, Christophe
Abstract : Polyethyleneimine methylenecarboxylate (PEI-MC) is explored as a possible new class of macromolecular decorporation agents in case of plutonium contamination. Abstract : Up until now, molecular chelating agents, such as diethylenetriamine pentaacetic acid (DTPA), have been the standard method for actinide human decorporation. Mainly active in blood serum, their distribution within the body is thus limited. To treat a wider range of organs affected by plutonium contamination, a potential new class of macromolecular decorporation agents is being studied. Polyethyleneimine methylenecarboxylate (PEI-MC) is one such example. It is being considered here because of its capacity for targeting the liver and bones.